2022
DOI: 10.2196/36337
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Patient Factors and the Effectiveness of Wearable Trackers at Increasing the Number of Steps per Day Among Adults With Cardiometabolic Conditions: Meta-analysis of Individual Patient Data From Randomized Controlled Trials

Abstract: Background Current evidence supports the use of wearable trackers by people with cardiometabolic conditions. However, as the health benefits are small and confounded by heterogeneity, there remains uncertainty as to which patient groups are most helped by wearable trackers. Objective This study examined the effects of wearable trackers in patients with cardiometabolic conditions to identify subgroups of patients who most benefited and to understand inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…This suggests that the use of wearable physical activity monitoring devices with feedback may help cardiovascular patients to increase their daily walking, overcoming common physical activity practice barriers such as inappropriate scheduling of proposed physical activity, lack of time and lack of infrastructures to practise. These results are consistent with a previous systematic review and meta-analysis: in patients with chronic CVD using a wearable device measuring physical activity, the number of daily steps significantly increased by 1300 steps/day27 and by 1656 in patients with cardiometabolic diseases (obesity, diabetes mellitus and CVD) 30…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This suggests that the use of wearable physical activity monitoring devices with feedback may help cardiovascular patients to increase their daily walking, overcoming common physical activity practice barriers such as inappropriate scheduling of proposed physical activity, lack of time and lack of infrastructures to practise. These results are consistent with a previous systematic review and meta-analysis: in patients with chronic CVD using a wearable device measuring physical activity, the number of daily steps significantly increased by 1300 steps/day27 and by 1656 in patients with cardiometabolic diseases (obesity, diabetes mellitus and CVD) 30…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with a previous systematic review and meta-analysis: in patients with chronic CVD using a wearable device measuring physical activity, the number of daily steps significantly increased by 1300 steps/day 27 and by 1656 in patients with cardiometabolic diseases (obesity, diabetes mellitus and CVD). 30 A recent meta-analysis of three RCTs of supposedly healthy subjects and patients (any human population of any age) using a pedometer or accelerometer also showed a significant increase in daily steps (n=211, +2587 steps/ day (95% CI: 916 to 5257); I 2 =74.6% and p=0.002). 53 An umbrella review showed an increase of 1800 steps/day and an increase of 40 min of walking per day in clinical and non-clinical populations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation